Training and Assistance on Packaging, Labeling, and Online Marketing of Msmes - Ery Teguh Prasetyo; Wastam Wahyu Hidayat; Amor Marundha; Pugo Bayu Prabowo (Asian Journal of Community Services, 2023)
Based on this problem, the purpose of implementing service activities is to increase the knowledge and skills (quality of human resources) of MSME actors through labeling training on packaging. The program of training and mentoring activities is carried out through five stages, namely socialization, preparation, implementation of activities, evaluation and reporting. The result of implementing this community service activity is increasing knowledge and creating product packaging labeling. The output targets to be achieved in community service this time are aspects of competency, increasing understanding and skills of human resources (HR) MSME actors and academic aspects, the results of activities will be reported and published in one of the national journals.